An open label trial of nemiralisib, an inhaled PI3 kinase delta inhibitor for the treatment of Activated PI3 kinase Delta Syndrome. (April 2023) - Begg, Malcolm; Amour, Augustin; Jarvis, Emily; Tang, Teresa; Franco, Sara Santos; Want, Andrew; Beerahee, Misba; Fernando, Disala; Karkera, Yakshitha; Sander, Clare; Southworth, Thomas; Singh, Dave; et al.
Abstract: Activated PI3Kδ Syndrome (APDS) is a rare inherited inborn error of immunity caused by mutations that constitutively activate the p110 delta isoform of phosphoinositide 3-kinase (PI3Kδ), resulting in recurring pulmonary infections. Currently no licensed therapies are available. Here we report the results of an open-label trial in which five subjects were treated for 12 weeks with nemiralisib, an inhaled inhibitor of PI3Kδ, to determine safety, systemic exposure, together with lung and systemic biomarker profiles (Clinicaltrial.gov: NCT02593539). Induced sputum was captured to measure changes in phospholipids and inflammatory mediators, and blood samples were collected to assess pharmacokinetics of nemiralisib, and systemic biomarkers. Nemiralisib was shown to have an acceptable safety and tolerability profile, with cough being the most common adverse event, and no severe adverse events reported during the study. No meaningful changes in phosphatidylinositol (3, 4, 5)-trisphosphate (PIP3; the enzyme product of PI3Kδ) or downstream inflammatory markers in induced sputum, were observed following nemiralisib treatment. Similarly, there were no meaningful changes in blood inflammatory markers, or lymphocytes subsets. Systemic levels of nemiralisib were higher in subjects in this study compared to previous observations. While nemiralisib had an acceptable safety profile, there was no convincing evidence of target engagement in the lung following inhaled dosing and no downstream effects observed in either the lung or blood compartments. We speculate that this could be explained by nemiralisib not being retained in the lung for sufficient duration, suggested by the increased systemic exposure, perhaps due to pre-existing structural lung damage. In this study investigating a small number of subjects with APDS, nemiralisib appeared to be safe and well-tolerated. However, data from this study do not support the hypothesis that inhaled treatment with nemiralisib would benefit patients with APDS.